Factors Involved in Decision-Making Dilemmas Faced by Parents of Children with Severe Asthma in PICU During the Development of Discharge Care Plans: A Phenomenological Study - Fan G; Yi M; Qiu X; Zhao J (Journal of Asthma and Allergy, 2023)
Guimei Fan,1 Mo Yi,2 Xiangmin Qiu,1 Jinfang Zhao1 1Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 2School of Nursing, Peking University, Beijing, People’s Republic of ChinaCorrespondence: Jinfang Zhao, Shandong Provincial Hospital Affiliated to Shandong First Medical University, #324 Jingwuweiqi Road, Huaiyin District, Jinan City, Shandong Province, 250021, People’s Republic of China, Email zjfcqt@qq.comPurpose: This study aims to explore the complicated decision-making dilemma and challenges confronted by parents of children suffering from severe asthma within the Pediatric Intensive Care Unit (PICU) when participating in the development of their children’s discharge care plans.Patients and Methods: Employing a phenomenological methodology, a purposive sampling was performed to engage with 17 parents who participated in in-depth and semi-structured interviews between October 2022 and February 2023. The transcripts of these interviews were transcribed into textual data, which was then subjected to Colaizzi’s seven-step analysis for meticulous coding and comprehensive thematic elucidation.Results: The comprehensive analysis of the factors involved in the intricate decision-making dilemmas faced by parents of children with severe asthma during the process of crafting discharge care plans in the PICU revealed five themes and eight sub-themes: 1) Complexity of asthma-related information; 2) Insufficient provision of comprehensive decision-making support; 3) Encountering negative emotions and wavering confidence; 4) Navigating realistic constraints impacting both parents and HCPs; 5) Balancing the advantages and disadvantages of various plans.Conclusion: Parents of children with severe asthma in the PICU encounter intricate and multifaceted decision-making dilemmas while engaging in the formulation of discharge care plans. These complexities significantly dampen their decision-making enthusiasm and introduce potential risks to the children’s prognosis and recovery. In the future, it is imperative to leverage the guidance provided by healthcare professionals (HCPs) in the decision-making process, develop tailored decision support tools specifically designed for the formulation of discharge care plans for children with severe asthma in the PICU.Keywords: severe asthma, parents, discharge care plan, decision-making dilemma, phenomenological study